DESIGN, SYNTHESIS, BIOLOGICAL EVALUATION, AND IN SILICO STUDY OF NOVEL UREA DERIVATIVES AS INHIBITORS OF CARBONIC ANHYDRASE AND ACETYLCHOLINE ESTERASE - AKBABA, Yusuf; KALIN, Ramazan (Studia Universitatis Babeș-Bolyai Chemia, 2022)
This study aimed to synthesize novel unsymmetrical urea derivatives containing biologically active tryptamine and phenethylamines and investigate their inhibition effects on human carbonic anhydrase (hCA) I and II isozymes as well as acetylcholinesterase (AChE). For this purpose, five different N,N'-dialkyl urea derivatives 18-22 were synthesized from tryptamine and substituted 2-phenethylamine. According to the results of inhibition, all of the synthesized urea derivatives effectively inhibited both hCA (I - II) and AChE enzymes at micromolar concentrations. The IC50 values for these molecules were determined to be in the range of 1.214-2.281 µM for hCA-I, 0.888-2.984 µM for hCA-II, and 0.309-0.816 µM for AChE. The most potent inhibitors against hCA-I and hCA-II isozymes are compound 18 (IC50: 1.214 µM; Ki: 0.984 ± 0.277 µM) and compound 19 (IC50: 0.888 µM, Ki: 0.564 ± 0.019 µM), respectively. Furthermore, compound 20 (IC50: 0.309 M and Ki: 0.470 ± 0.039 M) is the most effective AChE inhibitor. Molecular docking studies of compounds with the most effective inhibition were performed. The estimated binding energy values for compounds 18, 19, and 20 were calculated to be −7.81, -7.34, and -8.20 kcal/mol, respectively. Finally, the ADME studies were determined these compounds' physicochemical and pharmacokinetic descriptors and drug-like properties.